2012
DOI: 10.6061/clinics/2012(03)02
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem diagnosis of acute myocardial infarction in patients with acute respiratory failure - demographics, etiologic and pulmonary histologic analysis

Abstract: OBJECTIVES:Acute respiratory failure is present in 5% of patients with acute myocardial infarction and is responsible for 20% to 30% of the fatal post-acute myocardial infarction. The role of inflammation associated with pulmonary edema as a cause of acute respiratory failure post-acute myocardial infarction remains to be determined. We aimed to describe the demographics, etiologic data and histological pulmonary findings obtained through autopsies of patients who died during the period from 1990 to 2008 due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…[13] Autopsy studies by revealing the variable histopathological changes that occur in visceral organs in different disease processes facilitate improved understanding, making future diagnosis and correlation simpler. Of the 16 cases showing histological evidence of ischemic heart disease, corresponding lung histopathology revealed pulmonary edema and diffuse alveolar damage in 71.4%, similar to Soiero AM et al, [14] reiterating the fact that lungs are secondarily involved in all forms of terminal cardiac events.…”
Section: A 6bsupporting
confidence: 69%
“…[13] Autopsy studies by revealing the variable histopathological changes that occur in visceral organs in different disease processes facilitate improved understanding, making future diagnosis and correlation simpler. Of the 16 cases showing histological evidence of ischemic heart disease, corresponding lung histopathology revealed pulmonary edema and diffuse alveolar damage in 71.4%, similar to Soiero AM et al, [14] reiterating the fact that lungs are secondarily involved in all forms of terminal cardiac events.…”
Section: A 6bsupporting
confidence: 69%
“…Severe hypoxemia resulting from acute respiratory failure contributes to reducing oxygen supply, which would stimulate the sympathetic system and increase myocardial oxygen demand [ 39 , 40 ]. Indeed, postmortem studies have revealed that approximately 5–25% of patients who died from acute respiratory failure had experienced unobserved myocardial infarction [ 41 ]. Another possible mechanism is the proinflammatory state, where respiratory infectious agents can elicit an inflammatory pattern in atheromatous plaques [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute respiratory failure with consequent severe hypoxaemia contributes to reduce oxygen supply and determines activation of the sympathetic system, which increases heart rate, cardiac output, and contractility, factors that can increase myocardial oxygen demand [ 24 , 25 ]. Incidence of myocardial injury or infarction in critically ill patients may go unrecognized [ 26 ], as post-mortem studies have suggested, where a prevalence of undiagnosed acute myocardial infarction (AMI) ranging from 5% to 25% in patients who died from acute respiratory failure was observed [ 27 , 28 ].…”
Section: Acute Coronary Syndromes and Covid-19mentioning
confidence: 99%